Improving Health Communication for the Deaf and Mute Community in Stunting Prevention in Bengkala Village, Buleleng Regency, Bali Province - Ani Purwati; Suraya Mansur; Gita Ruslita (International Journal Of Community Service, 2025)
Bengkala Village in Buleleng Regency, Bali, is an inclusive village inhabited by the Kolok community, a deaf-mute group that has developed a local sign language system. This community faces serious challenges in accessing health information, particularly related to stunting prevention efforts. This article aims to identify inclusive and effective health communication strategies for people with disabilities in the local context. Disabled groups remain vulnerable due to limited communication access. Through an equity-based communication approach and a disability-inclusive development framework, health communication needs to be developed using visual media, local sign language, and community-based participatory strategies. The analysis also shows that legally based interventions, such as Presidential Regulation No. 72 of 2021 and Law No. 8 of 2016, are important stepping stones, although their implementation remains limited. This study emphasizes the importance of transforming health communication, not only to inform but also to transformative efforts in reaching marginalized groups like the Kolok community to reduce stunting rates equitably and inclusively.